2022
DOI: 10.5219/1738
|View full text |Cite
|
Sign up to set email alerts
|

Development and shelf-life assessment of soft-drink with honey

Abstract: This scientific work describes research that aims to determine the physicochemical parameters of homogenized honey and its safety indicators based on the determination of toxic metals and radionuclides. A series of experimental studies were conducted to develop and study recipes for honey water based on different types of honey collected in the Lviv region of Ukraine, namely acacia, buckwheat, sunflower, coriander, goldenrod, linden, and weeds. According to the results of experiments, it was found that the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As for the content of carbohydrates, their content is lower in sour cream with vegetable oils (by 1.7%) because this product consists of 40% food emulsion, which does not contain carbohydrates, and 60% cow defatted milk, which is a carrier of carbohydrates -lactose, being a growth medium for lactic acid bacteria during the fermentation of a normalized mixture [24], [25]. Currently, the reduced lactose content in the food product can positively affect the human body by preventing lactose intolerance [26], [27].…”
Section: Resultsmentioning
confidence: 99%
“…As for the content of carbohydrates, their content is lower in sour cream with vegetable oils (by 1.7%) because this product consists of 40% food emulsion, which does not contain carbohydrates, and 60% cow defatted milk, which is a carrier of carbohydrates -lactose, being a growth medium for lactic acid bacteria during the fermentation of a normalized mixture [24], [25]. Currently, the reduced lactose content in the food product can positively affect the human body by preventing lactose intolerance [26], [27].…”
Section: Resultsmentioning
confidence: 99%
“…Also, it should be noted that the lactose content, which ensures the process of lactic-acid fermentation [26], [27] in normalised mixtures, is sufficient to obtain fermented milk coagulum with a titrated acidity of 60 °T. The number of viable lactic acid bacteria in fat-containing fermented-milk bases and their organoleptic quality indicators are shown in Table 2 and Table 3.…”
Section: Figurementioning
confidence: 99%
“…found in higher concentrations were insecticides (neonicotinoids, then organophosphates), herbicides, and fungicides. These study results underline the need for continued monitoring of the pollutant substances in this product to determine the risks of pesticide exposure to the health of the pollinator, particularly the honey bees, ecosystems, and their potential consequences for human health and other nontarget organisms [21], [31]. Among the studied honey samples in which the pesticide residues were found, the highest percentage was the bee poly floral honey -76.7%, sunflower, and rapeseed honey -8.7 and 7.0%, respectively.…”
Section: Volume 17 806 2023mentioning
confidence: 99%
“…In addition, an account must be taken of the costs of public funds for controlling the pesticide circulation in the environment and food products. Thus, it may be concluded that if the total environmental, social, and economic costs for the pesticides to be used could be measured as a whole, the profitability of the pesticides to be used would be substantially lower [31].…”
Section: Introductionmentioning
confidence: 99%